Can Art Influence Global Health Policy? (Imaginations: Journal of Cross-Cultural Image Studies, 2020)
This article examines the influence of art on global vaccination policy, with a special focus on contemplative art, designed to get us to look at issues differently, and advocacy art, making the case for quite specific policies or programs. Ultimately it argues that because policy choices are influenced by ideas and emotions, there is room for art to be indirectly influential when combined with action by social movements, at least those built around specific diseases.
Keywords: art as political intervention; social movements; global health policy; global summits; public policy theory; emotion